Revisiting of planting dates for maximizing seed size potato (Solaum tuberosum) tuber yield as per changing climatic scenario - SADAWARTI, MURLIDHAR J; SINGH, RAJESH K; SAMADHIYA, R K; SINGH, S P; ROY, S; SINGH, VINAY; RAWAL, SANJAY; BUCKSETH, TANUJA; KUMAR, RAJ; CHAKRABARTI, S K (The Indian Journal of Agricultural Sciences, 2019)
Potato (Solaum tuberosum L.) varieties, viz. Kufri Chandramukhi, Kufri Sindhuri and Kufri Chipsona 1 were evaluated for seed production in west-central Indian conditions. Days to the emergence and 50 % emergence were delayed in 10 and 17 October plantings (10.6, 10.5 days and 16.9, 16.6 days, respectively) and in the variety Kufri Sindhuri (10.6 days and 16.5 days). 7 November planting recorded higher growth attributes like emergence, number of stems, compound leaves except plant height. Delayed planting resulted in the reduction of plant height. Among the varieties, Kufri Sindhuri and Kufri Chipsona-1 recorded significantly higher growth parameters, viz. stem number, compound leaves and plant height. Higher seed size and total tuber number and per ha yield were recorded in 17 October onward plantings over other 10 October planting and highest was in 7 November planting (355 and 634 thousand/ha and 19.33 and 24.63 t/ha seed size and total tuber number and weight, respectively). Severe mosaic, mild mosaic and off types in each date of planting and varieties were below maximum permissible limit as per Indian minimum seed certification standards. Aphid population (weekly) was below the critical limit in all date of plantings and varieties. Gwalior region of west-central India is most suitable for seed production under prevailing climatic situation for getting higher seed yield.